Studies in world religions : an introduction to Abrahamic traditions - Yousif, Ahmed F (IIUM Press, 2013)
Studies in World Religions: An Introduction to Abrahamic Traditions starts with a general introduction followed by an analytical probe into the meaning of the discipline of Comparative Religion and its significance, historical development and methodology. It takes an analytical approach in studying Judaism and Christianity from religious, historical, social and philosophical perspectives. What are some of the points of agreement between the two traditions, and what are some of the areas of contention? A Qur’anic perspective on both religions is briefly offered. References are made to both primary and secondary sources as well as classical and modern Islamic literature. The final part of this volume presents a comparative analysis of fundamentalism and fanaticism. What provisions are there in the religion of Islam for dealing with fundamentalist and fanatical elements within its community? How do Muslim and Western approaches differ in dealing with these movements? This part provides a response to these questions, in addition to defining the terms fundamentalism and fanaticism, identifying their causes, the Islamic view on fanatical groups and the relationship between fanaticism and contemporary Islamic revivalism, as well as providing suggestions for how to cure fanaticism.